De novo CoA biosynthesis is required to maintain DNA integrity during development of the Drosophila nervous system - Bosveld, Floris; Rana, Anil; van der Wouden, Petra E.; Lemstra, Willy; Ritsema, Martha; Kampinga, Harm H.; Sibon, Ody C. M. (Human molecular genetics, 2008)
In a forward genetic screen in Drosophila melanogaster, aimed to identify genes required for normal locomotor function, we isolated dPPCS (the second enzyme of the Coenzyme A biosynthesis pathway). The entire Drosophila CoA synthesis route was dissected, annotated and additional CoA mutants were obtained (dPANK/fumble) or generated (dPPAT-DPCK). Drosophila CoA mutants suffer from neurodegeneration, altered lipid homeostasis and the larval brains display increased apoptosis. Also, de novo CoA biosynthesis is required to maintain DNA integrity during the development of the central nervous system. In humans, mutations in the PANK2 gene, the first enzyme in the CoA synthesis route, are associated with pantothenate kinase-associated neurodegeneration. Currently, the pathogenesis of this neurodegenerative disease is poorly understood. We provide the first comprehensive analysis of the physiological implications of mutations in the entire CoA biosynthesis route in an animal model system. Surprisingly, our findings reveal a major role of this conserved pathway in maintaining DNA and cellular integrity, explaining how impaired CoA synthesis during CNS development can elicit a neurodegenerative phenotype.